(untitled) (PerCursos, 2025)
The presence of images, especially photographs, is a prominent feature of contemporary life. In geographical education, they prove to be powerful resources for encouraging a critical reading of space and understanding the organization of socio-spatial phenomena. This article focuses on the problematic of limited inclusion of visual practices in geographical education, despite their didactic potential. Additionally, this article is based on the theoretical contributions of some authors such as: Lynch, regarding the image of the city; Sontag, on the social role of photography; Gomes, on visuality in geographical science; and Cavalcanti, on teaching about the city and Geography. One of the objectives of this research is to analyze how Geography teachers can produce photographic images for pedagogical purposes, turning those images into tools to interpret and teach urban space. Regarding the methodology, this qualitative research involved seven basic education teachers that participated in a formative study group, who also carried out photographic records in their cities and engaged in collective image analysis. It is noteworthy to notice that the choice of locations reflected the teachers’ experiences and perceptions, revealing different glances of the city. The results of the present study indicate that the act of photographing contributed to the problematization of the urban landscape and encouraged reflections on inequality, representations, and the city teaching. In conclusion, this study indicates that images expand the possibilities for reading the landscape and contribute to a more critical and meaningful pedagogical practice in geographical education.